Remediation of Old Substations for Arc Flash hazard - Zakir Husain; Deepak Kumar; Khushbu Thakur (International Journal of Applied Power Engineering (IJAPE), 2014)
Arc Flash is much different from the conventional shock hazard in the sense that it doesn’t involve direct contact of human beings with the live or energized part. The arcing energy involves high temperature of up to or beyond 20000K. This paper presents a case study of arc flash hazard analysis carried out in older industrial plant and the technological and work procedure changes that can be incorporated to reduce the incident energy level and thus provide a safer environment for the working personnels in plant.